PENGARUH MOTIVASI DAN KETERAMPILAN BERKOMUNIKASI TERHADAP PRESTASI BELAJAR MAHASISWA PADA TUTORIAL ONLINE BERBASIS PENDEKATAN KONTEKSTUAL PADA MATAKULIAH STATISTIKA PENDIDIKAN - Mery Noviyanti (Jurnal Pendidikan, 2011)
Student achievement for Statistics for education course at Universitas Terbuka (UT) is relatively low. Students need learning process that can increase learning motivation. Contextual approach is a learning process where students can understand the concept through its application in daily life which supposedly will increase learning motivation. Online tutorial is one of learning support services provided by the UT via the internet. By utilizing the discussion forums, initiation material, assignments and exercises, students can improve their communication skills so as to facilitate their learning. This article is based on the research which aimed to find out how motivation and communication skills influenced the learning achievement in online tutorials with contextual approach on Statistics for education course. Field trials were carried out in 36 undergraduate students who followed the online tutorials. The independent variable is motivation and communication skills, while the dependent variable is the learning achievement. Data were taken through questionnaires and observation and processed by means of regression test. The results showed that: a) motivation affect learning achievement by 88.7%, b) communication skills has a positive effect on learning achievement by 74.7%, and c) the influence of motivation and communication skills to the learning achievement was 89.7%.